If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -3) + -6x = 3(3x + 2) Reorder the terms: 3(-3 + 5x) + -6x = 3(3x + 2) (-3 * 3 + 5x * 3) + -6x = 3(3x + 2) (-9 + 15x) + -6x = 3(3x + 2) Combine like terms: 15x + -6x = 9x -9 + 9x = 3(3x + 2) Reorder the terms: -9 + 9x = 3(2 + 3x) -9 + 9x = (2 * 3 + 3x * 3) -9 + 9x = (6 + 9x) Add '-9x' to each side of the equation. -9 + 9x + -9x = 6 + 9x + -9x Combine like terms: 9x + -9x = 0 -9 + 0 = 6 + 9x + -9x -9 = 6 + 9x + -9x Combine like terms: 9x + -9x = 0 -9 = 6 + 0 -9 = 6 Solving -9 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 72+40=36+x | | 21+25m=28+18m | | 3y-6=2x+4 | | 13-17+24= | | 36-(2x+4)=2(x+6)+x | | 10-2(y-7)=3y+9 | | 150+20x=60+38x | | 32+x=-15 | | -(p+1)+5(p+8)=47 | | X+1.7=1.7x+22.9 | | 5-3(4x+3)=2 | | -(-2n-4)=5(n+2) | | 36=-9(10+1) | | 23=14+4n | | 5y^2+14=14 | | -(7n+1)-5(n+7)=12 | | 12+1.5x=15+.5 | | (7t-2)-(-3t+1)=-3-9t | | 3.5-0.02x=1.46 | | (-3)-(-14)=x | | 5x^2-25x-120=0 | | 3(u+w)+-5(u-w)= | | a(4-x)=0 | | 2x-4=8+4x | | 5(t-1)+2(t-1)=-2(t-2)+10(t+2) | | 4.9t^2+3t=5.2 | | 5*5.25=(k*5.75)+(5-k*4.50) | | 21+3*(2x-2)-2x=60-x | | 9y-2x=-11 | | 3(x+2)=2(3-x) | | 4(m+1)+7(-m+8)=75 | | 6+3x+3=15 |